2020
DOI: 10.3390/ijms21176088
|View full text |Cite
|
Sign up to set email alerts
|

Sephin1 Protects Neurons against Excitotoxicity Independently of the Integrated Stress Response

Abstract: Sephin1 is a derivative of guanabenz that inhibits the dephosphorylation of the eukaryotic initiation factor 2 alpha (eIF2α) and therefore may enhance the integrated stress response (ISR), an adaptive mechanism against different cellular stresses, such as accumulation of misfolded proteins. Unlike guanabenz, Sephin1 provides neuroprotection without adverse effects on the α2-adrenergic system and therefore it is considered a promising pharmacological therapeutic tool. Here, we have studied the effects of Sephin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 36 publications
2
5
0
Order By: Relevance
“…However, since Sephin1 did not affect the expression of ATF4, our findings challenge the thesis that Sephin1’s neuroprotective properties are mediated through the prolongation of the phosphorylation of eIF2α. Instead, our results align better with the conclusions of an increasing number of recent studies indicating that Sephin1 confers neuroprotection by attenuating the IRE1α branch of the UPR 36,37 , or by blocking the NMDA-induced neuronal death 53 .…”
Section: Discussionsupporting
confidence: 91%
“…However, since Sephin1 did not affect the expression of ATF4, our findings challenge the thesis that Sephin1’s neuroprotective properties are mediated through the prolongation of the phosphorylation of eIF2α. Instead, our results align better with the conclusions of an increasing number of recent studies indicating that Sephin1 confers neuroprotection by attenuating the IRE1α branch of the UPR 36,37 , or by blocking the NMDA-induced neuronal death 53 .…”
Section: Discussionsupporting
confidence: 91%
“… 16 , 57 , 58 Usage of Sephin1 in mammals can lead to a promotion of ISR activity; thus, it is used as a potential treatment in neuron motor-, and proteostasis-related diseases. 48 , 49 , 50 In our study, we found that the usage of Sephin1 in mice can lead to antitumor immunity suppression, which is most likely to be achieved by ISR process by single-cell expression analysis. In the C56BL/6 mice injected subcutaneously with B16F1 cells, the tumor growth rate in the Sephin1 group was significantly higher than that in the normal group, which indicated a possible relationship between the ISR process and antitumor immune activities.…”
Section: Discussionmentioning
confidence: 66%
“… 48 Because of its effect to PPP1R15A and ISR, Sephin1 is now used as a potential treatment in neuron-, motor-, and proteostasis-related diseases. 48 , 49 , 50 In this study, we used Sephin1 as an inhibitor of PPP1R15A to explore the effect of Sephin1 on the TIME, especially the impact on antitumor immune cells. We performed both in vivo and in vitro experiments and studied two different cell lines, B16F1 and 4T1.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Guanabenz and its derivatives (e.g., sephin1) have been shown to increase eIF2α phosphorylation [ 8 , 85 ]. Recent studies examining the therapeutic effect of Guanabenz and sephin1 have shown reductions in unfolded protein production, ER stress, and TBI neural deficits [ 86 , 87 , 88 , 89 , 90 ]. Additionally, Tauroursodeoxycholic acid (TUDCA), an endogenous bile acid, is another potential treatment targeting ER stress.…”
Section: Emerging Treatmentsmentioning
confidence: 99%